Pengaruh Optimum Stimulation Level dan Self-Monitoring Terhadap Impulsive Buying - Lu, Cen; Suwarno, Henky Lisan (Zenit, 2014)
The fast-growing tendency of shopping centers can be evidence that the economy of the community is going well. On the other hand, due to the large number of shopping centers, there is a stimulus for the community to do shopping activities more frequently. And if the shopping activities are done withoutgood planning, the activities can bring bad impacts. Consequently, they easily become more consumptive. In the field of marketing science, such behavior is called impulsive buying. Impulsive buying behavior is influenced by several factors, including both optimum stimulation level and selfmonitoring. Impulsivity is a tendency to act without thinking first, thus making cognitive decisions quickly, and fails to appreciate the situation. Optimum Stimulation Level is ownership that characterizes individuals in terms of their general response to environmental stimuli. Self-monitoringis the tendency to alter or adjust ones behavior in response to the presence or behavior of another. Hence, in this study, the researchers intend to predict impulsive buying consumers based on the analysis of two factors: optimum stimulation level and self-monitoring. To test this hypothesis, the researchers use multiple regressions. The results show that the optimum stimulation level has no positive effects on impulsive buying and self-monitoring has no negative effects on impulsive buying.Keywords: Optimum Stimulation Level, self-control, impulsive buying.